2018
DOI: 10.5539/jas.v10n5p353
|View full text |Cite
|
Sign up to set email alerts
|

Biofertigation of Forage With Effluents of Green Line of a Cattle Slaughterhouse: Microbial Diversity and Leaf Dry Mass Productivity

Abstract: The wastewater has been an environmental problem, but your used as fertilizers could reduce or eliminate the application of commercial fertilizers in soil. Arbuscular mycorrhizal fungi (AMF) and nitrogen fixing bacteria (NFB) are a good parameter to analyze the impacts of this fertigationon soil. We aimed to evaluate the distribution and diversity of AMF and NFB before and after applications of wastewater or manure from green line of a cattle slaughterhouse in the irrigation of B. brizantha cv Marandu in Cerra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…These results are due to the fact that bacteria fill an ecological niche composed of aerobic, facultative anaerobic and N-fixer microorganisms [56], which is much larger than that occupied by fungi. The same levels of microscopic fungi were reported by numerous authors in the superficial parts of bulks soils [60,61]. Generally, in agricultural soils, FF decrease at undetectable levels already at 20-30 cm, but in our anthropogenic soil samples, the absence of fungi was only recorded at a 30-50 cm depth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are due to the fact that bacteria fill an ecological niche composed of aerobic, facultative anaerobic and N-fixer microorganisms [56], which is much larger than that occupied by fungi. The same levels of microscopic fungi were reported by numerous authors in the superficial parts of bulks soils [60,61]. Generally, in agricultural soils, FF decrease at undetectable levels already at 20-30 cm, but in our anthropogenic soil samples, the absence of fungi was only recorded at a 30-50 cm depth.…”
Section: Discussionsupporting
confidence: 90%
“…These levels characterize commonly uncultivated soils [59,60]. In general, TMA decreased with depth and this finding is imputed to nutrient and oxygen limitations [61]. FF levels were 1 or 2 orders of magnitude lower than those of TMA.…”
Section: Discussionmentioning
confidence: 99%
“…The biological indicators' estimation in soil samples did not concern samples collected from 90-100 cm, because of small amount of microbial cell present at that depth. Carvalho et al (2018) did not observed bands in the DGGE profile of NFB and AMF genes at this soil depth. According to the authors, there was no viable fungal cell in the soil at a depth beyond 30 cm.…”
Section: Biological Indicators Of Soil Qualitymentioning
confidence: 49%
“…Moreover, this microbiota is responsible for the cycling of nutrients and energy flow in the soil (Moreira & Siqueira, 2006). Our research group is investigating the impacts of biofertigation management with wastewater of the green line on the soil microbiota (Carvalho et al, 2018). Note.…”
Section: Characmentioning
confidence: 99%